Kin discrimination and sex ratios in a parasitoid wasp. - Reece, SE; Shuker, D; Pen, I; Duncan, AB; Choudhary, A; Batchelor, C; West, SA (2004)
Sex ratio theory provides a clear and simple way to test if nonsocial haplodiploid wasps can discriminate between kin and nonkin. Specifically, if females can discriminate siblings from nonrelatives, then they are expected to produce a higher proportion of daughters if they mate with a sibling. This prediction arises because in haplodiploids, inbreeding (sib-mating) causes a mother to be relatively more related to her daughters than her sons. Here we formally model this prediction for when multiple females lay eggs in a patch, and test it with the parasitoid wasp Nasonia vitripennis. Our results show that females do not adjust their sex ratio behaviour dependent upon whether they mate with a sibling or nonrelative, in response to either direct genetic or a range of indirect environmental cues. This suggests that females of N. vitripennis cannot discriminate between kin and nonkin. The implications of our results for the understanding of sex ratio and social evolution are discussed.